Bulanık Mantık Yöntemiyle Sera Gölü Çevresinin Heyelan Duyarlılık Analizi - Aydın, Olgu; Raja, Nussaïbah Begum (Afet ve Risk Dergisi, 2024)
Landslides are a frequent occurrence in the Black Sea Region, mainly due to factors such as geomorphological and lithological conditions, soil properties and humidity, land use, along with effective precipitation. Landslide susceptibility assessments are vital to ensure that necessary precautions are taken to mitigate against landslides so as to help reduce possible loss of life and property. In addition, landslide susceptibility assessments are also important for future land development plans. The aim of the study is to carry out a landslide susceptibility assessment using the artificial intelligence-based Fuzzy Logic method of Sera Lake around Trabzon, Akçaabat district. The variables used in our model are: slope, aspect, slope shape, relative relief, lithology, distance to the river and topographic humidity index. The landslide susceptibility analysis of the Sera Lake environment provided an R2 value of 0.67 and RMSE and MAE values close to “0”. This suggests that our method was quite good at evaluating landslide susceptibility in our study area. Landslide sensitive areas correspond to an important part of the study area. The results of the study are important in terms of taking necessary measures against economic, social, cultural and environmental damages of landslides and making future plans in order to show the areas that may be sensitive to landslides.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Fuzzy Logic; Landslide; Landslide Susceptibility Map; Surrounding of Sera Lake